(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the allegorical nature of the story Planet of Hope by the Uzbek science fiction writer Khojiakbar Shaykhov. It analyzes the literary device of defamiliarization through which the author reinterprets environmental issues, including the destruction of the atmosphere’s protective layer, the irresponsibility of political institutions, and the inability of civilization to make proper use of scientific knowledge. The study identifies the parallel structure of the text the fate of the planet Nuvogap / the fate of Earth and reveals its function within the artistic system of the story. It is shown that Planet of Hope is one of the early examples of ecological science fiction in Uzbek literature and remains relevant in the context of contemporary environmental discourse.